Fractal characteristics of surface roughness and their effects on laser shock waves - Qingyong Zhu; Jinkun Zheng; Junjun Sun (AIP Advances, 2022)
The Weierstrass–Mandelbrot function model was used to simulate the rough topography of a target surface, and the fractal theory was used to study the fractal characteristics of the target surface topography, which is the self-similarity of surface topography. The 3D fluid dynamics governing equations of the laser-supported detonation plasma flow field in Cartesian coordinates are given and discretized by a high-order difference scheme. The equation of state of plasma under different conditions is considered, and a new method of flux splitting is introduced to carry out numerical simulations. The numerical results of plasma pressure, density, temperature, and velocity at different times and different surface roughnesses are obtained, which show the evolvement of the ablative plasma. The simulated results show that a rough surface can obviously affect the propagation velocity of the detonation wave near the wall. In addition, the waveform is also destroyed, forming a broken waveform.